EFL Second-Year University Students' Views of Skimming and Scanning Strategies in Enhancing Reading Efficiency (Comprehensive Journal of Science, 2026)
This study investigates the perceptions of second-year EFL university students regarding the use of skimming and scanning strategies in academic reading. Adopting a quantitative analytical research design, the study examines students' self-reported practices, perceived usefulness, and challenges associated with applying these strategies. Data were collected through a structured questionnaire administered to 25 EFL students at the Faculty of Education, Ajelat, University of Zawia.The findings indicate that the majority of participants view skimming and scanning as beneficial strategies for managing reading tasks and addressing time constraints, particularly in examination contexts. Students reported using skimming to gain a general understanding of texts and scanning to locate specific information efficiently. However, the results also reveal several challenges, including limited vocabulary knowledge and concerns about potentially missing important information. It is important to note that these findings reflect students' self-reported perceptions rather than objectively measured improvements in reading performance.The study concludes that skimming and scanning are perceived by EFL students as supportive strategies for efficient academic reading. It recommends providing clearer instructional guidance on the appropriate use and limitations of these strategies within university-level EFL reading instruction.
Keywords: Reading strategies, skimming, scanning, academic reading, quantitative study